Implementation and initial evaluation of village information system (openSID) utilization in West Sumbawa Regency - Wiryandito, Brian Abby Ariestyo; Fajrin, Maghfiroh; Firdaus, Muhammad Dimas (LP2M Universitas Islam Negeri Mataram, 2025)
[Bahasa]: Untuk mendukung tata kelola digital di wilayah perdesaan, Dinas Komunikasi dan Informatika (Diskominfo) Kabupaten Sumbawa Barat telah mengimplementasikan sistem informasi desa berbasis open source, OpenSID, di 65 desa dan kelurahan pada delapan kecamatan. Penulis terlibat langsung dalam proses implementasi, mencakup instalasi sistem, pelatihan operator, serta pendampingan teknis sebagai bagian dari program pengabdian kepada masyarakat. Penelitian ini bertujuan untuk mengevaluasi tingkat adopsi awal dan pemanfaatan sistem tersebut, khususnya pada aspek pengisian data kependudukan selama enam bulan pertama pasca-implementasi. Pendekatan kuantitatif digunakan dengan mengamati data statistik yang tersedia secara publik melalui situs resmi desa. Analisis dilakukan dengan membandingkan jumlah entri penduduk dalam sistem dengan estimasi jumlah penduduk tiap desa untuk mengukur progres pengisian data. Hasil menunjukkan adanya variasi signifikan antarwilayah, yang mencerminkan ketimpangan dalam pemanfaatan sistem. Ketimpangan ini berpotensi memengaruhi akses layanan publik digital dan efisiensi administrasi kependudukan di tingkat lokal. Studi ini menekankan pentingnya dukungan teknis berkelanjutan, pelatihan lanjutan, dan monitoring berkala guna memastikan keberhasilan dan keberlanjutan digitalisasi desa. Kata Kunci: OpenSID, sistem informasi desa, evaluasi pemanfaatan, data kependudukan, desa digital [English]: To support digital governance in rural areas, the Department of Communication and Information Technology (Diskominfo) of West Sumbawa Regency has implemented an open-source Village Information System, OpenSID, across 65 villages and sub-districts in eight districts. This study presents the implementation process and an initial evaluation of system utilization, focusing on population data entry during the first six months post-deployment. The author played an active role in the implementation, including system deployment, technical training, and mentoring of village operators as part of a structured community service program. A quantitative approach was used by observing publicly available statistical data from official village websites. The analysis measured data entry progress by comparing recorded population entries in the system with estimated village population figures. Findings reveal significant disparities among regions, indicating uneven system utilization that could lead to imbalances in access to digital public services and administrative efficiency. This study highlights the importance of technical support, continuous training, and regular monitoring to ensure the success and sustainability of rural digital transformation. The results offer practical insights for future policy development and replication in other rural regions. Keywords: OpenSID, village information system, utilization evaluation, population data, digital village